Design and implementation of a transmission protection protocol to improve the performance of wireless sensor networks in hybrid networks. (22nd December 2014) - Sheu, Jang–Ping; Wu, Shu–Hsun; Ma, Chuang; Hu, Wei–Kai
In hybrid networks, the devices of Wireless Local Area Networks (WLANs) and Wireless Sensor Networks (WSNs) will interfere with each other when working in a same area because they use the same band, 2.4 GHz. With the greater transmission power and more aggressive channel access time resolution, WLANs often affect the communication of WSNs severely. To eliminate this kind of interference effect, we design protection nodes and propose a transmission protection protocol, WSNs Transmission Protection Protocol (WTPP), to improve the transmission performances of WSNs in hybrid networks. The protection nodes can emit protection signal periodically to block the traffic of WLANs and permit the transmission of WSNs. We implement WTPP in a hybrid network testbed to prove its feasibility. Comparing with legacy ZigBee, the experimental results show that WTPP can improve the packet delivery ratio of WSNs efficiently under the interference of WLANs. When WSNs work on low duty cycle, the throughput degradation of WLANs is less than 6%.